THE EFFECT OF HEARDING BIAS AND OVERCONVIDENCE ON CRYPTOCURRENCY INVESTMENT DECISIONS WITH FINANCIAL LITERACY AS A MODERATING VARIABLE (Study on Tokocrypto Official Group Community) - Febrian Yoga Aditama; Surya Raharja (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of cryptocurrency as an investment instrument is increasingly attracting the attention of investors, especially among the digital community. However, investment decisions in this asset are often influenced by psychological biases, such as herding bias and overconfidence, which can lead to irrational and high-risk decision-making. This study aims to analyze the effect of herding bias and overconfidence on cryptocurrency investment decisions, with financial literacy as a moderating variable. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) to test the relationship between variables. Primary data were collected through questionnaires distributed online to members of the Tokocrypto Official Group community with a sample of 100 respondents selected using the snowball sampling technique. The results of the study show that herding bias has no significant effect on cryptocurrency investment decisions, while overconfidence has a positive and significant effect on investment decisions. However, financial literacy is not proven to significantly moderate the relationship between herding bias and overconfidence on investment decisions. This finding indicates that even though investors have a good level of financial literacy, psychological factors still play a dominant role in making investment decisions in cryptocurrency. This study contributes to enriching the literature on behavioral finance by revealing the limited role of financial literacy in suppressing psychological bias in risky investment decisions. The practical implications of this study emphasize the need for investment education that focuses not only on financial literacy, but also on controlling psychological aspects in investment decision making.